ANALISIS MANAJEMEN STRESS KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Inggrid Mentari Batu Bara; Susilawati Susilawati (CV. ADIBA ADISHA AMIRA, 2023)
Stress management is a way of thinking and reacting that is shown to overcome painful burdens or transactions caused by that stress. It is clear from this understanding that perceived stress will not become a burden or pressure if employees are able to cope with and manage stress properly. This research method is a systematic review, by collecting literature sources in the form of scientific journals or scientific papers published in the last five years and using D databases Electronics such as: open science faramework/OSF, Medline/Pubmed, Google Scholar and Google Scholar.The purpose of the literature study is to find out whether there is an influence between work stress management on employee job satisfaction. The results of the discussion show that job stress has a negative and significant effect on job satisfaction and employee performance, job satisfaction has a positive and significant effect on employee performance, job satisfaction positively and significantly mediates the effect of work stress on employee performance. When the stress felt by employees is low, it can increase job satisfaction, so that employee performance will increase.